PKM PENDAMPINGAN KEWIRAUSAHAAN BAGI UMKM BELITUNG SEBAGAI UPAYA MENDUKUNG SUSTAINABLE TOURISM - Mei Ie; Hetty Karunia Tunjungsari; Ariawan Gunadi; Anny Valentina (Jurnal Bakti Masyarakat Indonesia, 2022)
This community engagement activity was held to give entrepreneurial assistance for SMEs in Belitung as an effort to enhance sustainable tourism. Partners in this activity are the Belitung Regency Government or more precisely 100 SMEs assisted by the Center for Integrated Service of Small Medium Enterprises and Cooperatives in Belitung. This mentoring activity is part of the Funding Assistance for the Independent Learning Policy Research Program on the Independent Campus, and Community Service Based on Research Results for Private Higher Education in 2021, organized by the Directorate General of Higher Education Research and Technology, Indonesian Ministry of Education, Culture, Research and Technology. In this community engagement activity, the Tarumanagara University team consisting of lecturers and students from the Faculty of Economics and Business, the Faculty of Law and the Faculty of Fine Arts and Design provides assistance that results in improving the marketing quality of SMEs products. Methods of implementation of activities include the analysis stage, the mentoring stage, and the reporting stage. Mentoring activities are divided into four sessions with each session followed by twenty-five SMEs. In each session, activities are also carried out in parallel in three small groups. During the assistance, the PKM team conducted an interview to find out the strengths, weaknesses and potentials possessed by each SMEs. The output of this activity is in the form of works in the form of logos, banners (physical and digital), packaging labels, packaging and digital advertising for SMEs. Broadly speaking, the results of this activities are able to provide direct benefits for partners to promote their products and expand market share.ABSTRAK:Kegiatan PKM ini diselenggarakan untuk memberikan pendampingan kewirausahaan bagi UMKM di Belitung sebagai upaya mendukung sustainable tourism. Mitra dalam kegiatan ini adalah UMKM binaan Pusat Layanan Usaha Terpadu Koperasi dan Usaha Mikro, Kecil dan Menengah Kabupaten Belitung. Kegiatan pendampingan ini merupakan bagian dari kegiatan Bantuan Pendanaan Program Penelitian Kebijakan Merdeka Belajar Kampus Merdeka, dan Pengabdian Kepada Masyarakat Berbasis Hasil Penelitian Perguruan Tinggi Swasta Tahun 2021, yang diselenggarakan Ditjen Dikti Ristek, Kemdikbud Ristek. Dalam PKM ini, tim Universitas Tarumanagara yang terdiri dari dosen dan mahasiswa dari Fakultas Ekonomi dan Bisnis, Fakultas Hukum dan Fakultas Seni Rupa dan Desain memberikan pendampingan yang menghasilkan peningkatan kualitas pemasaran produk UMKM. Metode pelaksanaan kegiatan meliputi tahap analisis, tahap pendampingan, dan tahap pelaporan. Kegiatan pendampingan terbagi ke dalam empat sesi dengan masing-masing sesi diikuti oleh dua puluh lima UMKM. Dalam setiap sesinya, kegiatan juga dilakukan secara paralel dalam tiga kelompok kecil. Selama pendampingan, tim PKM melakukan wawancara untuk mengetahui kekuatan, kelemahan serta potensi yang dimiliki dari masing-masing UMKM. Luaran dari kegiatan ini adalah berupa karya dalam bentuk logo, banner (fisik dan digital), label kemasan, kemasan serta iklan digital bagi UMKM. Secara garis besar, hasil kegiatan PKM mampu memberikan manfaat langsung bagi mitra untuk mempromosikan produknya dan memperluas pangsa pasar.